Sistem Rekomendasi Pembelian Sepeda Motor Bekas Menggunakan Metode Fuzzy Tahani - Yuli Murdianingsih; Ulfah Sitiumayah (STMIK IKMI Cirebon, 2020)
A used motorcycle is an option in the quest to buy a motorcycle, reliability is one factor. Accessibility means the size and the sum of the installment. Affordability is very important given the Covid-19 pandemic and economic recession, particularly in an environment of economic downturn. This research aims to establish a used motorcycle purchase recommendation system using the year's criteria for the manufacture of used motorcycles, prices,Â and installments in the purchase of used motorcycles, as well as to assess how high the reliability of the used motorcycle purchase recommendation system is. Firstly, twenty used motor data were obtained which were used to analyze recommendations, secondly to determine the domain size, thirdly to determine the function and degree of membership for each parameter, fourth to measure fire intensity and fifth to determine recommendations for the purchase of used motorbikes. Testing device reliability using the MAE tool. The framework was implemented using the interface MySQL DBMS and PHP. Using the Fuzzy Tahani method, the search for used motorbikes can be carried out, with the benefit of providing the installment quantity parameter and fifty-eight percent of the device reliability for buying used motorcycles. Â